Answer:
x = 4 , y = -2
Explanation:
Solve the following system:
{5 x + 4 y = 12 | (equation 1)
3 x - 3 y = 18 | (equation 2)
Subtract 3/5 × (equation 1) from equation 2:
{5 x + 4 y = 12 | (equation 1)
0 x - (27 y)/5 = 54/5 | (equation 2)
Multiply equation 2 by 5/27:
{5 x + 4 y = 12 | (equation 1)
0 x - y = 2 | (equation 2)
Multiply equation 2 by -1:
{5 x + 4 y = 12 | (equation 1)
0 x+y = -2 | (equation 2)
Subtract 4 × (equation 2) from equation 1:
{5 x+0 y = 20 | (equation 1)
0 x+y = -2 | (equation 2)
Divide equation 1 by 5:
{x+0 y = 4 | (equation 1)
0 x+y = -2 | (equation 2)
Collect results:
Answer: {x = 4 , y = -2